2005
DOI: 10.1007/s10815-005-7202-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pentoxifylline in reducing oxidative stress-induced embryotoxicity

Abstract: Pentoxifylline may be beneficial in reducing hydrogen peroxide induced embryo damage and improve IVF outcome. Patients with endometriosis-associated infertility may benefit from the use of pentoxifylline without significantly affecting embryo development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 14 publications
0
24
2
Order By: Relevance
“…82 A dose-dependent decrease in % blastocyst development rate (BDR) was shown with increasing concentrations of H 2 O 2 indicating that H 2 O 2 (>60 lm) is embryotoxic. 83 In the clinical ART setting, various antioxidants such as vitamin E, 84 vitamin C, 85 cysteine, 86 and taurine and hypotaurine 87 when added to the culture medium have been shown to improve the developmental ability of the embryos by reducing the effects of ROS.…”
Section: Ros In Artmentioning
confidence: 99%
“…82 A dose-dependent decrease in % blastocyst development rate (BDR) was shown with increasing concentrations of H 2 O 2 indicating that H 2 O 2 (>60 lm) is embryotoxic. 83 In the clinical ART setting, various antioxidants such as vitamin E, 84 vitamin C, 85 cysteine, 86 and taurine and hypotaurine 87 when added to the culture medium have been shown to improve the developmental ability of the embryos by reducing the effects of ROS.…”
Section: Ros In Artmentioning
confidence: 99%
“…To evaluate the antioxidant effect of LC, two-to four-cell mouse embryos were exposed to toxic concentrations of H 2 O 2 (500 mmol/L) in the culture medium for 72 h. Hyrdogen peroxide at a concentration of 50 mmol/L is reported to significantly decrease BDR in two-cell mouse embryos (18). In our experiment we used tenfold higher concentrations recorded in the previous literature to examine the extent to which level LC can neutralize the oxidant effect of H 2 O 2 .…”
Section: Experiments 3: Antioxidant Effect Of Lcmentioning
confidence: 99%
“…It has been suggested that oxidative stress might play a role in endometriosis development and endometriosis-associated infertility (4,5). Reactive oxygen species (ROS) can also alter the embryonic development and lead to early embryo death (6)(7)(8). In this respect, diabetes, a condition characterized by high blood glucose concentrations, represents a model of oxidative stress related to embryo toxicity (9).…”
mentioning
confidence: 99%